Redescription of Micronephthys longicornis (Perejaslavtseva, 1891) (Annelida: Nephtyidae) - Dnestrovskaya, Nataliya Yu.; Jirkov, Igor A. (Zootaxa, 2019)
Micronephthys longicornis (Perejaslavtseva, 1891) is re-described on the base of topotypes. The distinguishing characters are: dentate barred chaetae with a peak in center of each bar (on first notopodia only), presence of two pairs of visible subdermal coalesced eyes middorsally in C3, branchiae absent; lyrate chaetae with unequal rami. It is shown that Micronephthys stammeri (Augener, 1932) should be accepted as its junior synonym.